Prospects and challenges in linseed (Linum usitatissimum L.) production: A review: PROSPECTS AND CHALLENGES IN LINSEED (LINUM USITATISSIMUM L.) PRODUCTION: A REVIEW - S A BIRADAR; K AJITHKUMAR; B RAJANNA; A S SAVITHA; G V SHUBHA; I SHANKERGOUD; B M CHITTAPUR; P K SINGH (Journal of Oilseeds Research, 2016)
Linseed or flax (Linum usitatissimum L.) is one of the most important industrial oilseed crops of India. It is grown either for the oil extracted from the seed or fibre from the stem. Every part of the linseed plant is utilized commercially either directly or after processing. Most of the oil is used in industry for the manufacture of paints, varnishes, inks and soaps and also used for edible purpose to a limited extent. The oil cake is a good feed for milch cattle and also used as manure. Linseed seed is widely used as a nutritive and functional ingredient in food products. Linseed in daily diet increases the level of a-linolenic acid (ALA) and omega-3 fatty acid which helps to reduce the risk of cardiovascular disease and cancer. AICRP on Linseed (ICAR) distributed in various agro-ecological situations in the country helped in introduction of new varieties adapted with appropriate production and protection technologies paved the way for introduction of the crop in different areas of the country and as component crop in cropping systems. It is possible to achieve higher yields and net monetary returns by adapting improved production technologies as demonstrated in FLDs conducted across the country. In this review, we have elucidated the production and protection technologies for improvement of linseed productivity in the country. The potential areas for future line of research are indicated for productivity improvement in linseed.